Isatuximab in the treatment of refractory and relapsed multiple myeloma: literature review and case report - Yu. E. Ryabukhina; P. A. Zeynalova; F. M. Abbasbeyli; O. L. Timofeeva; T. T. Valiev; N. A. Kupryshina; A. G. Zhukov (Онкогематология)
Multiple myeloma is a malignant tumor characterized by the proliferation of clonal plasma cells and currently remains an incurable disease, despite advances in therapy. Resistance and development of double refractoriness represent a significant problem, worsening the prognosis. To overcome double refractoriness, new proteasome inhibitors carfilzomib and ixazomib, the 3rd generation immunomodulator pomalidomide and monoclonal antibodies daratumumab, elotuzumab and isatuximab are used. Based on randomized phase III ICARIA-MM and IKEMA studies results, which demonstrated, along with a manageable safety profile, advantages in increasing the antitumor response depth, the rate of achieving negative minimal residual disease status and survival in all subgroups of patients with refractory/relapsed multiple myeloma, isatuximab is used in IsaPd (isatuximab, pomalidomide, dexamethasone) and IsaKd (isatuximab, carfilzomib, dexamethasone) combination. This article discusses the clinical pharmacology of isatuximab. The results of studies demonstrating the effectiveness and safety of antitumor therapy regimens including isatuximab, which made it possible to use it in clinical practice, are presented. We present a case report of a patient with refractory/relapsed multiple myeloma who received 3 lines of antitumor treatment, including class 2 proteasome inhibitors, lenalidomide and the monoclonal antibody elotuzumab. After 3 cycles of IsaPd (8 injections of isatuximab), partial remission and pain relief were recorded. The achieved antitumor effect, along with the absence of significant adverse events, facilitated the continuation of therapy at recommended doses.